دور الإصلاح الإداري في تحقيق التنمية المستدامة (دراسة ميدانية للعاملين صندوق الإعمار بنغازي) (Comprehensive Journal of Science, 2025)
The  paper is contains  on sum of mean  points related to the role of administrative reforming in sustainable development , it takes logical steps to views this stages of the study.                                                    at the beginning concentrate on the concepts of sustainable development, institutional reforming  generally, its properties , programs , which it gives to the countries which  suffering from the retardation , then throw light on the  difficulties  of  both reforming programs  and social development in this kind of societies with some examples to this problems.                     .                                                                                                                                                 In addition , identify the cultures factors and its impact on this countries , finally view the challenges which facing this programs reforming  ,the study use the questionnaire to collect the data of the study, and collect data by the comprehensive survey method, then use the( spss), to analyze the data, the result proves that institutional reform has role to achieving sustainable development  .
Keywords: sustainable development , administrative reforming